Experimental determination of metal fuel point defect parameters - Fluss, M.J.; McCall, S.K. (Вопросы атомной науки и техники, 2009)
Nuclear metallic fuels are one of many options for advanced nuclear fuel cycles because they
provide dimensional stability, mechanical integrity, thermal efficiency, and irradiation resistance
while the associated pyro-processing is technically relevant to concerns about proliferation and
diversion of special nuclear materials. In this presentation we will discuss recent success that we
have had in studying isochronal annealing of damage cascades in Pu and Pu(Ga) arising from the
self-decay of Pu as well as the annealing characteristics of non-interacting point defect
populations produced by ion accelerator irradiation. Comparisons of the annealing properties of
these two populations of defects arising from very different source terms are enlightening and
point to complex defect and mass transport properties in the plutonium specimens which we are
only now starting to understand as a result of many follow-on studies. More importantly
however, the success of these measurements points the way to obtaining important mass
transport parameters for comparison with theoretical predictions or to use directly in existing and
future materials modelling of radiation effects in nuclear metallic fuels. The way forward on
such measurements and the requisite theory and modelling will be discussed.
We bring to the attention of the reader that this article is based wholly or in part on earlier
publications of the authors. Ядерне металеве паливо є одним із багатьох варіантів прогресивного ядерного
паливного циклу, оскільки воно забезпечує розмірну стабільність, механічну цілісність,
тепловий коефіцієнт корисної дії і радіаційну стійкість, в той час, як піротехнологія
технічно відноситься до проблем про розповсюдження спеціальних ядерних матеріалів та
їх перенасичення. У даному повідомленні ми обговоримо останні успіхи, досягнуті нами
при вивченні ізохронного відпалу каскадів пошкоджень в Pu і Pu(Ga), які виникають в
результаті саморозпаду Pu, а також характеристики відпалу невзаємодіючих точкових
дефектів, які утворились при опроміненні у прискорювачі іонів. Порівняння цих двох
популяцій дефектів, виникаючих при різних вихідних умовах, проливають світло та
вказують на складні властивості дефектів і масопередачі в зразках плутонію, які ми
починаємо розуміти тільки зараз у результаті багатьох модифікованих досліджень, Однак,
і це більш важливе, успіх цих вимірювань вказує шлях отримання важливих параметрів
масо переносу для порівняння з теоретичними прогнозуваннями, або для безпосереднього
використання при моделюванні радіаційних ефектів у вже існуючих та майбутніх
матеріалах у якості ядерного металевого палива.
Ми звертаємо увагу читача на те, що ця стаття заснована повністю або частково на
більш ранніх публікаціях авторів. Ядерное металлическое топливо является одним из многих вариантов прогрессивного
ядерного топливного цикла, поскольку оно обеспечивает размерную стабильность,
механическую целостность, тепловой коэффициент полезного действия и радиационную
стойкость, в то время, как пиротехнология технически относится к проблемам
распространения специальных ядерных материалов и их перенацеливания. В данном
сообщении мы обсудим последние успехи, достигнутые нами при изучении изохронного
отжига каскадов повреждений в Pu и Pu(Ga), которые возникают в результате самораспада
Pu, а также характеристики отжига невзаимодействующих точечных дефектов,
образованных при облучении в ускорителе ионов. Сравнения этих двух популяций
дефектов, возникающих при разных исходных условиях, проливают свет и указывают на
сложные свойства дефектов и массопередачи в образцах плутония, которые мы только
сейчас начинаем понимать в результате многих модифицированных исследований.
Однако, что более важно, успех этих измерений указывает на путь получения важных
параметров массопереноса для сравнения с теоретическими предсказаниями или для
непосредственного использования при моделировании радиационных эффектов в уже
существующих и будущих материалах в качестве ядерного металлического топлива.
Мы обращаем внимание читателя на то, что эта статья основана целиком или частично
на более ранних публикациях авторов.